Seasonal divergence in reproductive timing on the verge of spring: comparing hypothalamic transcriptome of two seasonally sympatric North American songbird populations - Singh, Devraj; Fudickar, Adam M.; Ketterson, Ellen D. (Frontiers in Physiology, 2025)
Every year as spring approaches and day length increases, many birds begin to reproduce, an annual expression of seasonal phenology that requires physiological preparation. In species distributed over a broad geographic range, populations that breed at higher latitudes are often migratory and delay reproduction until later in the year as compared to those breeding at lower latitudes. Dark-eyed Juncos serve as an excellent model for understanding the timing mechanisms regulating population-level variation in seasonal reproductive responses. We compared two seasonally sympatric dark-eyed junco populations in early spring. One migrates (Junco hyemalis hyemalis) and breeds in Alaska and Canada, while the other remains resident (Junco hyemalis carolinensis) and breeds in the Appalachian Mountains of Virginia USA. These populations exhibit different photoperiodic responses to the same environment with respect to activation of the HPG axis, leading to earlier gonadal recrudescence in the resident population. We caught co-wintering sympatric male migrant (n = 6) and resident (n = 7) juncos from the field in March and collected the hypothalamic tissues. We also collected blood samples to determine circulating testosterone and a wing feather to determine stable isotope ratios (δ2H) as estimate of breeding latitude. We found three differentially expressed genes, among which gonadotropin releasing hormone 1 (GnRH1) showed significantly higher expression in early breeding residents as compared to migrant juncos. The δ2H showed a positive linear correlation with testosterone levels and GnRH1 mRNA, providing strong evidence for latitudinal variation in breeding phenology. This study provides insight into the underlying neuroendocrine response giving rise to a population-level difference in the timing of reproduction observed in a seasonally sympatric (co-wintering) population of resident and migrant juncos.